Beycesultan Excavations. Second Preliminary Report, 1955. Pottery and Stratifications. Some Preliminary Notes on the New Sequence - Lloyd, Seton
Late Bronze Age Complex on the Palace Hill — Remains of the Burnt Palace in Level V (Constructions — The Plan) — Individual Chambers or Units (The “Painted” Hall — The “Painted Loggia” — Large Light-area — South-western Unit — West Wing in Trench “K”) — Dating Level V by Stratigraphy — Relations with Cretan Architecture — “Wings” and “Insulae” — Main Entrances — Pillared Halls — Upper Story — Walls — Roofing — Conclusion; by J. Mellaart.